Absence of the LRRK2 mutation in Emirati Parkinson’s disease patients in contrast to other Arab populations - Metta, Vinod; Soorajkumar, Anjana; Loney, Tom; Nassir, Nasna; Chaudhuri, K. Ray; Uddin, Mohammed Jashim; Benamer, Hani T. S. (Frontiers in Aging Neuroscience, 2025)
BackgroundThe role of genetic factors in the pathogenesis of Parkinson’s disease (PD) is characterized by heterogeneity in specific genetic variations and their prevalence across different populations and geographic locations.ObjectiveTo investigate the frequency of the Leucine-rich repeat kinase 2 (LRRK2) mutation, a well-known genetic risk factor for PD, within Emirati patients.MethodsEmirati PD patients were recruited from the United Arab Emirates between September 2022 and May 2024. Blood samples were systematically screened for mutations across all 52 exons of the LRRK2 gene.ResultsThe LRRK2 mutation was not detected in any of the 50 Emirati PD patients (mean age 64.2 ± 14.1 years, of whom 56% are male) examined.ConclusionThe absence of the LRRK2 and specifically the G2019S mutation in Emirati PD patients corroborates findings from Saudi Arabia and indicates a distinct genetic pattern compared to other Arab regions like Egypt and Maghreb (North African) countries, where the G2019S mutation prevalence ranges from 10 to 40%. This underscores the need for further research to unveil alternative genetic determinants specific to the Emirati PD population.